Perancangan Interior House of Fashion Tiffani Meymorisa di Surabaya - Velica Jesslyn Tendean; Cok Gede Padmanaba; Grace Mulyono (Intra, 2016)
Tiffani Meymorisa is one of the young designers in Surabaya that is growing to meet the needs of fashion which has become a trend for the community lately and in accordance with the budget and with regard to the improving marketability of design as well as business potential with their supporting facilities. Therefore, a place where designer can sell their design to the public and meet the need of fashion with provided facility is needed. The existing interior problem is that the space is not adequate, such as less facilities, cramped and mixed work space, no room for special fitting, less space for storage, poor lighting at dusk, main entrance is not welcoming the customers, so a solution is needed by designing a supporting interior and facilities that can welcome and give the quality impression of the designer, giving the facility to be able to develop his work to be more recognized by people of Surabaya in accordance with the target market, provide comfort and ease in working and visiting. The concept is taken from the problems and the character of the designer, Tiffani Meymorisa. Elegant fashion design concept by Tiffani Meymorisa is also the concept for the interior design by lifting the concept of “Elegancy of Vogue”. Characters from Tiffani Meymorisa itself is applied to shapes, colors, and the atmosphere in the room. This design maximizes the application of Tiffani Meymorisa characters in each facility and its design, so that people can feel that the design quality of Tiffani Meymorisa is different with other designers.